Benefits of Education at the Intensive Margin: Childhood Academic Performance and Adult Outcomes among American Immigrants - Deniz Gevrek; Z. Eylem Gevrek; Cahit Guven (Institute for the Study of Labor (IZA), 2014)
Using the Children of the Immigrants Longitudinal Study (CILS), we examine the association between education at the intensive margin and twenty pecuniary and non-pecuniary adult outcomes among first- and second-generation American immigrant youth. Education at the intensive margin is measured by two widely used standardized math and reading test scores, national percentile rankings on these tests and cumulative grade point average (GPA) in both middle and high school. Our findings provide evidence that the academic achievement of immigrant children in early adolescence is an accurate predictor of later life outcomes. We also examine a novel hypothesis that relative academic performance of immigrant children in high school compared to middle school, which could be an indicator of change in adolescent aspirations and motivation as well as the degree of adaptation and assimilation to the host country, has an effect on their adult outcomes even after controlling for the levels of academic performance in middle and high school. The results suggest that an improvement in GPA from middle school to high school is associated with favorable adult outcomes. Several sensitivity tests confirm the robustness of main findings.
Keywords: I2; J15; J24; 330; economics of education; human capital; immigrant well-being; immigrant academic performance; immigrant assimilation